Knowledge, attitudes, and practices of Indonesian residents regarding COVID-19: A national cross-sectional survey - Yodang Yodang; Stefanus Mendes Kiik; Achmad Fauji; Hamka Hamka; Rizky Meuthia Pratiwi; Nuridah Nuridah; Rahmad Yusuf; Yossi Fitrina (Intelektual Pustaka Media Utama, 2021)
Coronavirus disease (COVID-19) infection has been a major public health-related issue worldwide, including Indonesia. The COVID-19 cases still escalating until this study finished in June 2020 due to the disease positively spreading from person to person. To reduce the spreading of the disease, investigating Indonesian’s knowledge, attitudes, and practice on COVID prevention and mitigation during the outbreak period was crucial. A survey cross-sectional was conducted and using social networking apps to recruit participants. All Indonesian residents who have 18 years old and over and living in Indonesia during the COVID-19 outbreak were voluntarily invited to participate in this study. There are 3464 participants involved in this study. The mean age was 27.63 years, and mostly were women, domicile in Java, held bachelor degrees, students, Muslims, and single/never married. The lowest mean practices score was found among residents who live in Maluku, Papua, and Papua Barat, senior high qualification, unemployed, indigenous religions, and single/never married. The majority of Indonesian residents have good knowledge, positive attitudes, and good practice to promote COVID-19 prevention and mitigation to reduce the pandemic spreading within the country. However, there is a lack of knowledge, attitudes, and practice among a particular group of participants.